2021
DOI: 10.1080/09540105.2021.1874884
|View full text |Cite
|
Sign up to set email alerts
|

A novel polysaccharide from plant fermentation extracts and its immunomodulatory activity in macrophage RAW264.7 cells

Abstract: Plant fermentation extracts (PFEs) produced from fermenting various fruits and vegetables by microorganisms have traditionally been consumed as healthy beverages in Asia. Herein, the immunomodulatory activities of a novel polysaccharide (AP) isolated from PFE were examined in RAW264.7 cells. The results showed that AP was composed of Rha, Xyl, Man and Glu in a molar ratio of 9.7:27.6:8.81:53.85 and the average molecular weight was 4.81 × 10 5 Da. Our data showed that AP could significantly enhance the phagocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…This suggests that fermentation enhances the immunomodulating activity. Liang Y et al’s [ 41 ] research showed that a polysaccharide from plant fermentation extracts could significantly enhance the phagocytic activity and secretion of NO, iNOS, TNF-α, IL-6, and IL-10 of RAW264.7. Xie L et al’s [ 42 ] study showed that the polysaccharides from liquid fermentation of Monascus purpureus 40,269 could activate RAW264.7 cells, promoting the secretion of reactive oxygen species, NO, IL-1, TNF-α, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that fermentation enhances the immunomodulating activity. Liang Y et al’s [ 41 ] research showed that a polysaccharide from plant fermentation extracts could significantly enhance the phagocytic activity and secretion of NO, iNOS, TNF-α, IL-6, and IL-10 of RAW264.7. Xie L et al’s [ 42 ] study showed that the polysaccharides from liquid fermentation of Monascus purpureus 40,269 could activate RAW264.7 cells, promoting the secretion of reactive oxygen species, NO, IL-1, TNF-α, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…The FITC-Dextran (1 mg/mL) was added to the cell culture medium of each group and cultured at 37 °C for 1 h [ 50 ]. Cells of each group were washed twice with ice-cold PBS and centrifuged at 1000 rpm for 5 min.…”
Section: Methodsmentioning
confidence: 99%